IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MENGATASI KRISIS MORAL PADA MATA PELAJARAN PPKn DI SEKOLAH SMP NEGERI 1 LUAHAGUNDRE MANIAMOLO T.A 2022/2023 - Sri Astuti Zega (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2023)
The problem of this research is the occurrence of a moral crisis in students in the learning process. The results of this research show that studying character education in Civics subjects can overcome students' moral crises. Therefore, it may be inferred that character education is being implemented in the Civics curriculum at SMP Negeri 1 Luahagundre Maniamolo, namely: a. Provide coaching to students. b. Give awards or appreciation to students who are successful in applying character values. c. Provide an example to students. d. Creating a democratic school environment. e. Create comfort for students. f. Provide a good approach. Even though there are many efforts made by teachers to implement character values ​​and overcome moral crises, there are still obstacles that teachers face. This obstacle is the lack of children's seriousness in learning, this makes it difficult for teachers to apply character education to learning, for example the child's attitude is indifferent towards the teacher during learning. The suggestion from researchers is that schools should be able to create a comfortable school environment to make it easier to instill character education for students.